Formação e implantação dos consórcios intermunicipais em saneamento: um estudo de três experiências no Brasil - Ana Piterman (2014)
This study aims to investigate the formation and implementation of three sanitation consortia in Brazil in light of the new scenario established both by the Public Consortia Act n. 11.107/05 and the National Sanitation Act n. 11.445/07. The consortium agreement is seen as an opportunity for the municipalities to fulfill their obligations under the National Sanitation Act and to achieve universal sanitation coverage. In this context, this work explores the following question: Can the public consortium be profitably employed by small municipalities in order to enhance their technical, administrative and operational capacities in supplying clean water and providing sanitation services? The conceptual framework is based on theoretical works of the social capital field. Three consortia were selected for analysis, namely CISMAE Paraná, CISAB MG e CORESA Sul do Piauí. The research applied qualitative methods. Semi-structured interviews were conducted, as fieldwork, with professionals and public employees selected for their importance in the formation and operation of the consortia. The collected data were analyzed using thematic content analysis. The results showed that public inter-municipal consortia are important tools to stimulate the deployment and management of sanitation public policies. The benefits brought by consortia to the municipalities are manifold: rationalization of the socio economic, technological and human resources, greater transparency in resources management, legal certainty, financial sustainability, and political empowerment, among others.